Extracellular Vesicles from a Biofilm of a Clinical Isolate of Candida albicans Negatively Impact on Klebsiella pneumoniae Adherence and Biofilm Formation - Marianna Imparato; Angela Maione; Annalisa Buonanno; Renato Gesuele; Noemi Gallucci; Maria Michela Corsaro; Luigi Paduano; Angela Casillo; Marco Guida; Emilia Galdiero; Elisabetta de Alteriis (Antibiotics, 2024)
The opportunistic human fungal pathogen Candida albicans produces and releases into the surrounding medium extracellular vesicles (EVs), which are involved in some processes as communication between fungal cells and host–pathogen interactions during infection. Here, we have conducted the isolation of EVs produced by a clinical isolate of C. albicans during biofilm formation and proved their effect towards the ability of the Gram-negative bacterial pathogen Klebsiella pneumoniae to adhere to HaCaT cells and form a biofilm in vitro. The results represent the first evidence of an antagonistic action of fungal EVs against bacteria.